The rights of the wife in the Quranic text - BA-Shraheel, Muna Awadh (Journal of Humanities & Social Sciences, 2022)
In our study, we raised a number of questions about how the Qur’anic text depicts the wife, what rights the wife granted her and how they were organized, and how compatible they are with our Muslim social reality. We have determined the goal of the study in clarifying the rights of the wife in the Qur’anic text and trying to compare it with reality through scientific observation. To achieve the goal and answer the questions, we made use of the symbolic interactive theory and the functional theory that is most involved in family issues, with the help of which we studied the reality of the wife’s rights in the Qur’anic text, in the psychological and social direction and then its financial direction. This study is one of the studies of religious sociology. Hence the importance of the social study of the rights of the wife in the Qur’an. Because this is not an easy matter and requires an extraordinary religious and intellectual effort for fear of touching mistakes. Therefore, we relied on the content analysis with great caution, and we reached a number of results, which we summarize as follows: The Qur’anic text defines social and psychological rights that make her live in peace, affection and mercy, including, for example, the right to guardianship over her, and her right to divorce when life with the husband becomes impossible. It also specified for her material rights that were not preceded by other legislation, such as her right to inheritance, and the advantage of managing her financial affairs. Do not be based on one of her money only when she wants. The Qur’anic text also regulated the wife’s rights to divorce, as it did not give the husband the full right to control her life by limiting the number of divorces, and it preserved her rights during breastfeeding and nursery by the necessity of spending on her and her clothing. Despite the clarity of the wife’s rights in the Qur’anic text- in some Muslim families- it prevents the wife from empowering her.